Pendampingan Penyusunan Laporan Keuangan bagi UMKM - Sharon, St Salmah; Syam, Asriah; Sanapang, Gracela Marisa; Monalisa, Monalisa; Suade, Yuyun Karistin Meilisa (STIE Malangkucecwara, 2024)
This community service aims to strengthen the empowerment of Micro, Small, and Medium Enterprises (MSMEs) in South Sulawesi through assistance in preparing financial statements. Through a series of workshops, trainings, and individual mentoring sessions, we provide an in-depth understanding of the significance of financial statements and equip MSME owners with practical skills to compile, read, and analyze their financial statements. The mentoring method involves organizing interactive workshops led by experienced financial practitioners and individual mentoring sessions tailored to the needs of each MSME. In addition, we provide online resources as a learning platform that MSMEs can access flexibly, including guides, financial statement templates, and relevant case studies. Outcomes of the service include improved MSMEs' understanding of financial reporting, significant financial empowerment, and increased access to external financial support. MSMEs that participated in the program were able to produce clear financial statements, providing a basis for smarter decision-making and increasing their chances of securing financial support from financial institutions. With a focus on the context of South Sulawesi, this service contributes to the strengthening of the MSME sector in the region, supports local economic growth, and positively impacts the financial sustainability of MSMEs. Through assistance in preparing financial statements, it is hoped that MSMEs in South Sulawesi can develop sustainably and contribute optimally to regional economic development